Comprehensive analysis on the relation of marketing and distribution of ACI Logistics Limited-Lifestyle. - Faruk Mahadi, Md Omar (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.